Criação, desenvolvimento e validação da escala de autopercepção de capacidade para luta - CAMPOS, Jorge William de Sá (2024)
INTRODUCTION: In order to improve the performance of recreational practitioners and athletes of fights, it becomes increasingly common to practice evaluations to understand individual aspects, level of physical fitness, the objectives related to the sport, in this sense it is important to develop tools more directed to the modalities, understanding their individual characteristics. OBJECTIVE: To create, develop and verify the measurement properties of the Self-Perceived Fighting Capacity Scale (SEFICAS), which aims to evaluate the self-reported fighting capacity of practitioners of fighting, martial arts and combat sports. METHODS: This is a study of the creation and validation of a questionnaire following the guidelines of the Consensus-based Standards for the selection of health Measurement Instruments (COSMIN). To create the questionnaire, content validity was performed using the Delphi method. Exploratory factor analysis was used to verify the structure of the SEFICAS. To perform the construct validity, the SEFICAS score will be correlated with the score of other questionnaires already validated for the Brazilian population. For the test-retest reliability analysis, a subsample of 50 participants will be used who will respond to SEFICAS in two moments, with an interval of 7 days. The intraclass correlation coefficient and Cronbach's alpha were the measures of reliability and internal consistency used respectively. RESULTS: We recruited 104 volunteers from 11 states and the Federal District, of which 77.90% were male and 21.10% were female. The unidimensionality of the instrument was identified (KMO = 0.91, p < 0.001 in the Bartlett sphericity test) and adequate values (>0.40) were observed for factorial loadings related to the domain. The construct has a magnitude between -0.247 and 0.505, a result of the correlation between SEFICAS, the 8 domains of SF-36 and SEFIP-sport. The analysis of reliability (ICC= 0.91) and internal consistency (Cronbach's alpha 0.94) reached adequate values. We did not observe ceiling and floor effects (values above 15%) in the present study. CONCLUSION: The results point to the adequacy of SEFICAS to evaluate the fighting capacity of athletes and practitioners of martial arts and combat sports in Brazil.